Achieving autobiographical form : a twentieth century perspective - Meihuizen, Nicholas (Costerus., 2016)
In Achieving Autobiographical Form Nicholas Meihuizen argues that significant autobiographies achieve significant forms, peculiar to themselves alone. Form, he argues, is not accidental or merely functional. The author arrives at a form through a careful negotiation between the self's immersion in its world and its ability to distance itself from this world. The quality of the resultant self-scrutiny enables the author to transform everyday reflex into the act of attention that results in formal achievement, a uniquely crafted structure. Meihuizen's book helps demonstrate how each piece of autobiographical writing under consideration in it (works by Yeats, Conrad, Martin Amis, Frank Kermode, Andrew Motion, Roy Campbell, Richard Murphy, and J.M. Coetzee) discovers a unique form.